Main Character’s Resistance Against Traumatic Experience in Frances Hudgson Burnett’s The Secret Garden: Freud’s Tripartite Model Analysis - Brian Cesar (Vivid: Journal of Language and Literature, 2018)
This thesis discusses about the effect caused by parent’s neglect towards children’s development as seen in the novel The Secret Garden by Francis Hudgson Burnett. The main character, Mary Lennox, has life without love and attention from her parents. This situation has a great impact towards Mary’s development, mentally and physically. The role of “the secret garden” along with several characters that appears in the story have a big contribution in help Mary to change to a better person, based on the theory by Sigmund Freud about “id, ego and superego” or famous with the term “tripartite theory”. The result of this research is how the contribution from the secret garden to help Mary changes to a better child. The secret garden has a role to helps Mary understands about her own intention, helped with the other minor characters that drives the “id” and “superego” of the main character.